Agriculture and Employment Creation: Evidence from Nigeria - Ebere, Chidinma Edith; Ajibola, J. O.; Onakoya, A. B. (EuroEconomica, 2022)
In this study, an investigation has been made regarding nexus between agriculture and generated employment in Nigeria from 1990 to 2019, utilizing Dynamic Ordinary Least Squares. The summary of findings in this study could be stated as follows; agricultural value added (AVA) and rate of unemployment had a positive relationship which is significant at 10% level of significance in Nigeria. Government expenditure on agriculture and rate of unemployment had a significant positive relationship in Nigeria. Inflation rate (INF) and exchange rate (EXR) showed a positive and significant impact on unemployment except foreign direct. By and large, it could be submitted that agriculture did not contribute to employment generation in Nigeria. In view of the above findings, this recommendation is made for the Nigerian policy makers, revamping of agriculture via massive investment in this sub sector of the economy is urgently needed in Nigeria before it could ensure employment generation in the country.